2008
DOI: 10.1177/0032885507310994
|View full text |Cite
|
Sign up to set email alerts
|

The Sociopolitical Context of Prison Violence and Its Control

Abstract: This research explores the sociopolitical context of prison violence and its control in the state of Illinois, and discusses the series of events that led to the opening of a supermax prison. Interrupted time series analyses were used to test whether the use of the supermax was associated with declines in prison violence, controlling for the potentially confounding influence of a systemwide effort to restructure the Illinois Department of Corrections following a prison scandal in 1996. There was no association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Briggs et al (2003) concluded that the opening of supermax prisons—highly restrictive facilities designed to house those with especially violent or disruptive behavior—in three states had no effect on violence between incarcerated people. The results regarding assaults targeting staff were mixed, with Arizona experiencing a short-term increase, Illinois experiencing a long-term decrease (see also Sundt et al, 2008), and Minnesota showing no change. Similarly, Huebner (2003) found no relationship between the use of solitary confinement at the facility level and self-reported assault on staff or other incarcerated people.…”
Section: Disciplinary Segregation and Institutional Misconductmentioning
confidence: 99%
See 1 more Smart Citation
“…Briggs et al (2003) concluded that the opening of supermax prisons—highly restrictive facilities designed to house those with especially violent or disruptive behavior—in three states had no effect on violence between incarcerated people. The results regarding assaults targeting staff were mixed, with Arizona experiencing a short-term increase, Illinois experiencing a long-term decrease (see also Sundt et al, 2008), and Minnesota showing no change. Similarly, Huebner (2003) found no relationship between the use of solitary confinement at the facility level and self-reported assault on staff or other incarcerated people.…”
Section: Disciplinary Segregation and Institutional Misconductmentioning
confidence: 99%
“…Despite its popular use as a tool to control incarcerated people’s behavior, there is not much evidence for the effectiveness of disciplinary segregation at reducing misbehavior. Rather, several studies have concluded that segregation is unrelated to institutional misconduct or related to higher levels of misconduct (Briggs et al, 2003; Huebner, 2003; Labrecque & Smith, 2019; Lucas & Jones, 2019; Meyers et al, 2023; Morris, 2016; Motz et al, 2021; Steiner & Cain, 2016; Toman, 2022; Wooldredge & Steiner, 2015; but see Steiner, 2009; Sundt et al, 2008). This study seeks to add to our understanding of the relationship between disciplinary segregation and misconduct by empirically testing whether and how misconduct varied after changes were made to Minnesota Department of Corrections’ (MnDOC) policies regarding the use of disciplinary segregation.…”
Section: Introductionmentioning
confidence: 99%
“…Shalev (2009, p. 69) Supermax prisons are highly secure facilities that house people in complete isolation for 22-24 h per day for months or years at a time. The proliferation of supermax across state corrections systems trailed behind the emergence of "tough on crime" punishment policies, as prison systems became more crowded, grew more heterogeneous, and faced new disorder problems (Feeley & Simon, 1992;Garland, 2013;King, 1999;Phelps, 2011;Sundt et al, 2008). Modern corrections systems and staff working in them argue that supermax prisons are needed to reduce serious forms of prison disorder, such as violence, escape attempts, and contraband sales (Riveland, 1999;Sundt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of supermax across state corrections systems trailed behind the emergence of "tough on crime" punishment policies, as prison systems became more crowded, grew more heterogeneous, and faced new disorder problems (Feeley & Simon, 1992;Garland, 2013;King, 1999;Phelps, 2011;Sundt et al, 2008). Modern corrections systems and staff working in them argue that supermax prisons are needed to reduce serious forms of prison disorder, such as violence, escape attempts, and contraband sales (Riveland, 1999;Sundt et al, 2008). Concerns about violence and disorder are used to support the scale of supermax use and which people are sent there.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, acts of violence have negative psychological consequences for the victim, including depression and shame. Researchers now believe prison culture can prevent or provoke violence, and a prison’s culture can be changed through effective interventions (Beck & Johnson, 2012; Sundt, Castellano, & Briggs, 2008; Wolff & Shi, 2009). Mindfulness meditation training for inmates might be among the most effective of these interventions, helping to prevent violence, improve quality of life, and reduce recidivism.…”
Section: Introductionmentioning
confidence: 99%